Genotypic Detection of Dominant Bacteria in Dental Caries in Uyo, Nigeria - Udoh, Mary Athanasius; Onwuezobe, Ifeanyi Abraham; Abdulkadir, Rasheedat; Abubakar, Auwal; Yahaya, Musbau Adekunle; Onah, Daniel Oche (Darul Yasin Al Sys, 2025)
Dental caries remains one of the most prevalent and persistent oral health challenges globally, with nearly universal incidence across populations. The disease is increasingly complicated by the emergence of antibiotic-resistant bacteria, a phenomenon largely driven by biofilm formation and the acquisition of resistance genes. This study aimed to identify the predominant bacterial species implicated in the etiology of dental caries in Uyo, Nigeria, and to characterize their associated antibiotic resistance genes. A total of 120 clinical samples were analyzed using the VITEK 2 Compact System (bioMérieux) for bacterial identification and antibiotic susceptibility testing. Molecular detection of three extended-spectrum β-lactamase (ESBL) genes—CTX-M, TEM, and OXA—was performed via PCR using standard thermal cycling conditions on an ABI 9700 Applied Biosystems platform. Among the 27 isolates recovered, Gram-negative bacteria constituted 66.7%, with Burkholderia cepacia complex being the most prevalent (25.9%). Burkholderia cepacia exhibited high sensitivity to Amikacin and Tobramycin but showed marked resistance to Ceftazidime. Of the B. cepacia isolates, 6 (85.7%) underwent 16S rRNA sequencing, confirming their identity as Burkholderia cepacia (n=4) and Burkholderia cenocepacia (n=2). CTX-M genes were detected in all sequenced isolates (100%), while TEM genes were present in one isolate (16.7%) and OXA genes were absent. These findings underscore the potential public health threat posed by ESBL-producing B. cepacia complex strains in dental caries, highlighting the urgent need for targeted antimicrobial stewardship and enhanced surveillance in oral healthcare settings.